PENYULUHAN PENGGUNAAN ALAT PENGHEMAT DAYA LISTRIK PADA RUMAH TANGGA - Simon Patabang; Jeremias M. Leda; Syaban Ramadhan (Gapenas Publisher, 2023)
Power tools in the house are very helpful to do the job quickly in every household. As the use of electrical equipment increases, monthly electricity bills tend to increase. To overcome this problem, partners are interested in buying an electric power saving device because it is promised that this tool can save electricity bills by 30% to 45%. However, after using it for several months, the partner felt disappointed because the electricity bill did not decrease. To help partners, counseling is carried out about electrical knowledge related to electric power-saving devices and energy-saving electrical equipment. The outreach aims to increase partners' knowledge about saving electrical power in the household. From the results of the counseling, it is known that partners are able to understand the use of electricity-saving devices so that they are expected to help others to avoid the influence of the promotion of electricity-saving devices. Partners also understand the function of electricity-saving equipment in an effort to reduce electricity bill costs. Efforts to save electricity consumption in households require partner awareness and discipline on the importance of saving electrical energy so that they can regulate the use of electrical devices according to their needs at any time